Analisis Rute Jalan Efektif di Kabu Paten Nabire Provinsi Papua Tengah Menggunakan QGIS - Sandri Marta Saba; Gunawan Prayitno (STMIK Pesat Nabire, 2026)
Nabire Regency in Central Papua Province confronts significant geographical complexities in transportation system development, characterized by hilly topography and limited road infrastructure that impacts community mobility efficiency. This research analyzes road route optimization through Geographic Information System (GIS) approach using QGIS 3.28.3 software with QNEAT3 plugin for network analysis. The research methodology applies network analysis considering multiple parameters including travel distance, travel time, road surface conditions, slope gradients based on Digital Elevation Model (DEM), and impedance factors according to infrastructure quality. Spatial data were obtained from Geospatial Information Agency (BIG) and OpenStreetMap (OSM) with analysis focusing on 8 origin-destination pairs representing critical movements to health facilities, education centers, and economic hubs. Analysis results identified alternative routes demonstrating 12.5-20% travel time efficiency compared to existing routes, with an average optimization of 15.7%. Field validation confirmed model prediction accuracy with error rates below 8%. These research findings provide strategic recommendations for local government in sustainable transportation infrastructure planning that can enhance regional accessibility and support local economic development in the Central Papua region.